أثر الصادرات الزراعية على مؤشر التنويع الاقتصادي دراسة قياسية للدول النفطية 2004-2023 - زهرة دلباني; كير نجيبة (university of eloued جامعة الوادي, 2025)
تهدف هذه الدراسة إلى قياس مدى تأثير الصادرات الزراعية على التنويع الاقتصادي لستة دول ريعية، من خلال التركيز على تحليل تطور كل من الصادرات الزراعية والتنويع الاقتصادي، ومن أجل تحديد هذا الأثر فقد تم تقدير النموذج القياسي المرتبطة بالمتغيرات المتمثلة في الصادرات الزراعية كمتغير مستقل ومؤشر التنويع الاقتصادي كمتغير تابع خلال الفترة 2004- 2023، بالاعتماد على المنهج الوصفي والتحليلي, حيث تم استخدام نماذج بانل الديناميكي، فخلصت الدراسة إلى أنه هناك أثر عكسي (سالب) للصادرات الزراعية في دعم التنويع الاقتصادي في الاجل القصير حسب نموذج PMGأما في الأجل الطويل فالأثر طردي (موجب) بدول العينة خلال الفترة المدروسة. This study aims to measure the impact of agricultural exports on economic diversification in six rentier states. This is achieved by analyzing the evolution of both agricultural exports and economic diversification. To determine this impact, an econometric model was estimated using agricultural exports as the independent variable and the economic diversification index (HHI, where a higher value indicates increased concentration and thus reduced diversification) as the dependent variable, covering the period 2004-2023. Dynamic panel models were employed for the estimation. The study concluded that, according to the PMG model, there is an inverse (negative) effect of agricultural exports in supporting economic diversification in the short run. However, in the long run, the effect is direct (positive) for the sample countries during the studied period.
Keywords: تنويع اقتصادي; صادرات زراعية; اقتصاد ريعي; مؤشر هيرفندال; هيرشمان; Economic diversification; agricultural exports; rentier economy; Dutch disease، Herfindahl-Hirschman index